Hubungan Antara Motivasi, Sikap, dan Kecerdasan Adversitas dengan Hasil Belajar Biologi Peserta Didik Kelas XI SMA - Hasniar, Hasniar; Hala, Yusminah; Syamsiah, Syamsiah (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to analyze the relationship between learning motivation, learning attitude, and adversity quotient with biology learning outcomes of eleventh grade students at SMA Negeri 1 Makassar. The research method used is ex-post facto with a correlational nature. The population of this study consists of all students of SMA Negeri 1 Makassar totaling 1212 students. The sample of the study is the eleventh grade science class determined using the Slovin formula, with a sample size of 132 students. Data collection involved instruments measuring learning motivation, learning attitude, and adversity quotient comprising 90 items of statements and documentation. The research findings revealed a correlation coefficient of 0.809, indicating a strong relationship between the variables.